Microorganisms associated with hedgehog arthropods - Linda Benkacimi; Adama Zan Diarra; Jean-Michel Bompar; Jean-Michel Bérenger; Philippe Parola (Parasites & Vectors, 2023)
Abstract Hedgehogs are small synanthropic mammals that live in rural areas as well as in urban and suburban areas. They can be reservoirs of several microorganisms, including certain pathogenic agents that cause human and animal public health issues. Hedgehogs are often parasitized by blood-sucking arthropods, mainly hard ticks and fleas, which in turn can also carry various vector-born microorganisms of zoonotic importance. Many biotic factors, such as urbanization and agricultural mechanization, have resulted in the destruction of the hedgehog’s natural habitats, leading these animals to take refuge near human dwellings, seeking food and shelter in parks and gardens and exposing humans to zoonotic agents that can be transmitted either directly by them or indirectly by their ectoparasites. In this review, we focus on the microorganisms detected in arthropods sampled from hedgehogs worldwide. Several microorganisms have been reported in ticks collected from these animals, including various Borrelia spp., Anaplasma spp., Ehrlichia spp., and Rickettsia spp. species as well as Coxiella burnetii and Leptospira spp. As for fleas, C. burnetii, Rickettsia spp., Wolbachia spp., Mycobacterium spp. and various Bartonella species have been reported. The detection of these microorganisms in arthropods does not necessarily mean that they can be transmitted to humans and animals. While the vector capacity and competence of fleas and ticks for some of these microorganisms has been proven, in other cases the microorganisms may have simply been ingested with blood taken from an infected host. Further investigations are needed to clarify this issue. As hedgehogs are protected animals, handling them is highly regulated, making it difficult to conduct epidemiological studies on them. Their ectoparasites represent a very interesting source of information on microorganisms circulating in populations of these animals, especially vector-born ones. Graphical abstract